The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/15248372.2020.1814293
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Development in Children’s Scientific Reasoning: Results from a Three-Year Longitudinal Study

Abstract: Scientific reasoning refers to the thinking skills involved in conceiving and conducting an investigation. This study examined how proficiency in performing these skills develops during the upper-elementary school years. A sample of 157 children (age 7-10) took a performancebased scientific reasoning test in three consecutive years. Four distinct developmental patterns emerged from their annual test scores, which were independent of prior domain knowledge and sociodemographic characteristics except gender. Dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
4
25
0
Order By: Relevance
“…This study found that scientific reasoning developed overall linearly, with significant developmental progression between all grades of elementary school and no large clusters of children with nonlinear development. In line with previous longitudinal work in 8-to 10-year-olds (Lazonder et al, 2020), there was a group of children with nonlinearly developing scientificreasoning abilities (Cluster 1), who can be described as "late bloomers." These children revealed no progress in scientific reasoning between K1 and G1, but a steep increase between G1 and G3.…”
Section: Development Of Scientific Reasoningsupporting
confidence: 82%
See 4 more Smart Citations
“…This study found that scientific reasoning developed overall linearly, with significant developmental progression between all grades of elementary school and no large clusters of children with nonlinear development. In line with previous longitudinal work in 8-to 10-year-olds (Lazonder et al, 2020), there was a group of children with nonlinearly developing scientificreasoning abilities (Cluster 1), who can be described as "late bloomers." These children revealed no progress in scientific reasoning between K1 and G1, but a steep increase between G1 and G3.…”
Section: Development Of Scientific Reasoningsupporting
confidence: 82%
“…One of the few longitudinal studies that addresses scientific reasoning in late elementary school (involving children aged 8-10 years) found four distinct developmental patterns: high and low achievers, and early and late bloomers. These patterns were independent of domain knowledge, math abilities, and the parental education level, and only weakly correlated with the developmental patterns for reading abilities (Lazonder et al, 2020), making it impossible to predict which children would be high or low achiever, or early or late bloomers. Research is needed to identify the beneficial and necessary starting conditions influencing the onset of the development of scientific reasoning.…”
Section: Scientific Reasoning: Early Abilities General Cognitive Abil...mentioning
confidence: 94%
See 3 more Smart Citations